UPAYA GURU UNTUK MENGEMBANGKAN KEMANDIRIAN ANAK USIA DINI DI GUGUS HIPORBIA - Anggun Kumayang Sari; Nina Kurniah; Anni Suprapti (Jurnal Ilmiah POTENSIA, 2016)
The research has aimed to describe efforts of the teacher to develop autonomy of early childhood at gugus Hiporbia Ratu Samban District of Bengkulu City. Method that has used in the research is descriptive quantitative. The research has used total sampling method, with 30 teachers at gugus Hiporbia Ratu Samban District as sample. The data has obtained by questioner, and analized used precentage.  Result of the research has shown that teacher’s efforts to develop autonomy of the early childhood at gugus Hiporbia Ratu Samban District of Bengkulu City was conducted by effort preventif (66%), effort development (29%), effort kuratif (5%). Based on these result it is recommended to teachers to develop the child’s autonomy with regard effort preventif and effort kuratif. Whereas for subsequent research can investigate more about effort preventif and kuratif in more depth.